PARAMETERS FOR DETERMINING GERMAN LANGUAGE SKILLS AND ABILITIES IN ACADEMIC LYCEUMS WITH KARAKALPAK LANGUAGE OF LEARNING - Sadikova, Azada Bekbergenovna (SCIENCE and SOCIETY, 2026)
This article is devoted to the issues of assessing the skills and abilities in German in academic lyceums with the Karakalpak language of instruction. The main criteria for assessing are the fulfillment of the assigned task, the coherence and continuity of the work performed, and the quality of the presentation of the idea itself.